Distinctive pattern of white matter injury in neonates with rotavirus infection. (6th January 2015) - Yeom, Jung Sook; Kim, Young-Soo; Seo, Ji-Hyun; Park, Ji Sook; Park, Eun Sil; Lim, Jae-Young; Woo, Hyang-Ok; Youn, Hee-Shang; Choi, Dae Seob; Chung, Ju-Young; Han, Tae-Hee; Park, Chan-Hoo
Abstract : Objective: To report a consecutive series of neonates with seizures or apnea and displaying white matter injuries with distinctive magnetic resonance diffusion-weighted imaging (DWI) pattern, and to discuss the high positive rate of rotavirus infection seen in these patients. Methods: In a retrospective review of neonates who were admitted to a tertiary referral center with seizures or apnea, we found a distinctive pattern of white matter injury (symmetrical restricted diffusion in the periventricular white matter and white matter tracts including the corpus callosum) in 18 patients. We describe the clinical and laboratory features of these 18 neonates. Additional PCR analyses for rotaviruses and parechoviruses were performed on banked frozen samples of CSF of 4 patients and blood of 15 patients. Results: All 18 patients were born at term and healthy until symptoms occurred 4–7 days after birth. No history of asphyxia was observed. Only 1 patient presented with fever, and no patient showed a rash. All patients except 1 (94.4%) were rotavirus-positive in stool samples. However, neither rotaviruses nor enteroviruses/parechoviruses were detected in the CSF and blood. Tissue loss was observed in 5 of 8 subjects on repeat MRI scans. Conclusions: Neonates with this distinctive DWI pattern had a high positive rate of rotavirus infection, without evidence of other pathogens, and were characterized as term newborns with neurologic symptoms arising approximately the fifth day after birth. Although the specificity of this pattern is unclear, rotavirus testing should be considered for neonates presenting with this DWI pattern.